Political Dynamics in Health Policy Planning in Konawe Kepulauan Regency - Ramadhan Tosepu; Rini Agustia Amin (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2026)
Background: Political dynamics play a critical role in shaping health policy planning, particularly in decentralized governance settings where multiple actors, interests, and institutional constraints interact. In Indonesia’s island regions, limited evidence exists on how political processes influence local health policy planning. Understanding these dynamics is important for strengthening inclusive and responsive health governance. Objectives: This study aimed to analyze the political dynamics influencing health policy planning in Konawe Kepulauan Regency, Indonesia, with particular attention to leadership, power relations, stakeholder participation, and structural challenges shaping policy processes. Methods: This study employed a qualitative case study design using an interpretive approach. Data were collected through in-depth semi-structured interviews with six purposively selected informants representing government, legislature, professional organizations, and civil society actors involved in health policy planning. Relevant policy documents were also reviewed to complement interview data. Data were analyzed using thematic analysis following Braun and Clarke’s framework, supported by the interactive model of Miles and Huberman. Results: The findings generated four major themes: political governance in health policy planning, power relations and political negotiation, community participation and inclusive governance, and structural and political challenges in health planning. Executive leadership emerged as a dominant force in agenda setting and priority determination, while policy planning involved negotiation among multiple actors through budgeting and deliberative processes. Participatory mechanisms, particularly community forums and stakeholder engagement, contributed to more inclusive planning. However, fiscal limitations, political will, and health system capacity constraints significantly shaped policy feasibility and implementation. Conclusion: Health policy planning in Konawe Kepulauan Regency is shaped not only by technical considerations but also by complex political dynamics involving leadership, negotiation, participation, and structural constraints. Understanding health planning through a political governance lens highlights the importance of collaborative and context-sensitive approaches to strengthen decentralized health policy processes. Keywords: health policy planning; political dynamics; collaborative governance; decentralization; local governance